HBCD and TBBPA in particulate phase of indoor air in Shenzhen, China - Ni, Hong-Gang; Zeng, Hui (The Science of the total environment, 2013)
Hexabromocyclododecane diastereoisomers (α, β, and γ-HBCD) and tetrabromobisphenol A (TBBPA) were investigated in air conditioning filter dust (designated as particulate phase of indoor air, PPIA) collected from an office building in Shenzhen, China in 2009. Concentrations of ΣHBCD (sum of α-, β-, and γ-HBCD) ranged from 652 to 122, 973ng/g in PPIA. Generally, γ-HBCD was the most abundant diastereomer. Concentrations of TBBPA ranged from 30 to 59, 140ng/g in PPIA. According to our results, approximate 61.9pg/kg body weight/day (pg/kg/d) PM2.5 bound ΣHBCD can be inhaled deep into the lungs and 31.3pg/kg/d PM10 bound ΣHBCD tends to be deposited in the upper parts of the respiratory system, and those values of TBBPA were 28.7pg/kg/d and 14.5pg/kg/d for the lower and upper respiratory tracts, respectively. The average intakes of ΣHBCD via dust inhalation and ingestion were 37.92pg/kg/d and 2, 079pg/kg/d for adults, and those data of TBBPA were 17.62pg/kg/d and 966.2pg/kg/d, respectively. Our research found that exposure via indoor dust inhalation and ingestion contributed more than dietary pathway. Sensitivity analysis result suggests that the concentration of HBCD and TBBPA is the most significant parameter governing estimated results, and the other parameters, such as body weight and inhalation rate, do not affect the outcome much. •HBCD and TBBPA in indoor air dust (PPIA) in Shenzhen, China were measured.•Indoor dust contributes more to human exposure to HBCD and TBBPA than diet.•The level of HBCD and TBBPA is the most key factor governing exposure estimation.